Bullying and Harassment perceived by undergraduate nursing students in clinical settings, and its Implication to Academic Strategies and Interventions - Qutishat, Mohammed Ghalib; Kannekanti , Saraswathi (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Background: Bullying and Harassment are unwanted aggressive behavior of people working in organizations, colleges and in public settings. People who undergo this may have severe effects on their physical, psychological and social status. Which can reduce the work output and at pointed times it may end up with suicides. Aim: To examine the extent of bullying and Harassment perceived by nursing students in clinical training in Oman. Method: A descriptive cross-sectional design was used. A sample of 118 undergraduate nursing students was recruited from Sultan Qaboos University in Oman; the questionnaire consisted of the participants’ socio-demographic background and Student Experience of Bullying during Clinical Placement (SEBDCP). Results: Overall, 53.4% of students reported that they had experienced bullying or Harassment behaviors at least once during their clinical training period. Nursing students experienced Bullying and Harassment experienced mostly at the hospital settings 38.1% (n=118) followed by Schools 22% (n=118) and communities 21 % (n=118). It was mainly reported by students that Verbal and Nonverbal bullying was the most common type of bullying behavior they experienced. It was found that 28% (n=118) of the students reported that their working and the slandered of patient care were negatively affected. Conclusion: Experiences of bullying impacts nursing students especially in the clinical settings can negatively influence patient care and the quality of nursing education. It is a long-standing problem within the nursing profession.